Oxa Analogues of Nexturastat A Demonstrate Improved HDAC6 Selectivity and Superior Antileukaemia Activity. (25th March 2021) - Pflieger, Marc; Sönnichsen, Melf; Horstick‐Muche, Nadine; Yang, Jing; Schliehe‐Diecks, Julian; Schöler, Andrea; Borkhardt, Arndt; Hamacher, Alexandra; Kassack, Matthias U.; Hansen, Finn K.; Bhatia, Sanil; Kurz, Thomas
Abstract: The acetylome is important for maintaining the homeostasis of cells. Abnormal changes can result in the pathogenesis of immunological or neurological diseases, and degeneration can promote the manifestation of cancer. In particular, pharmacological intervention in the acetylome with pan‐histone deacetylase (HDAC) inhibitors is clinically validated. However, these drugs exhibit an undesirable risk‐benefit profile due to severe side effects. Selective HDAC inhibitors might promote patient compliance and represent a valuable opportunity in personalised medicine. Therefore, we envisioned the development of HDAC6‐selective inhibitors. During our lead structure identification, we demonstrated that an alkoxyurea‐based connecting unit proves to be beneficial for HDAC6 selectivity and established the synthesis of alkoxyurea‐based hydroxamic acids. Herein, we report highly potent N ‐alkoxyurea‐based hydroxamic acids with improved HDAC6 preference compared to nexturastat A. We further validated the biological activity of these oxa analogues of nexturastat A in a broad subset of leukaemia cell lines and demonstrated their superior anti‐proliferative properties compared to nexturastat A. Abstract : A hydroxylamine connecting unit facilitates HDAC6 preference : The derivatization of nexturastat A with alkoxyurea connecting units is reported. This modification resulted in an increased preference for HDA6 and increased antiproliferative properties in haematological cancer cell lines.